Against the Tedium of Immortality. - Bruckner, DonaldW. (International Journal of Philosophical Studies, 2012)
In a well-known paper, Bernard Williams argues that an immortal life would not be worth living, for it would necessarily become boring. I examine the implications for the boredom thesis of three human traits that have received insufficient attention in the literature on Williams’ paper. First, human memory decays, so humans would be entertained and driven by things that they experienced long before but had forgotten. Second, even if memory does not decay to the extent necessary to ward off boredom, once-satisfied desires often return after a sufficient period of time. Eternity would always contain sufficient time for our desires to rejuvenate. Third, even if too many of our desires were satisfied but not yet rejuvenated, we can expect that human ingenuity would continue to invent new pursuits, pastimes, careers, and ways of life that would prevent us from becoming bored as we moved from one to another. Finally, I consider and respond to several objections, including the claims that as much variety as I propose to be put into an eternal life is inconsistent with having one character throughout one’s life and that the sort of character change and memory decay I postulate is inconsistent with personal identity.